Ten years' clinical experience with biosimilar human growth hormone: a review of efficacy data - López-Siguero JP; Pfäffle R; Chanson P; Szalecki M; Höbel N; Zabransky M (Dove Medical Press, 2017)
Juan Pedro López-Siguero,1 Roland Pfäffle,2 Philippe Chanson,3 Mieczyslaw Szalecki,4,5 Nadja Höbel,6 Markus Zabransky6 1Servicio de Endocrinología Pediátrica, Hospital Materno-Infantil, Hospital Regional Universitario de Málaga, Spain; 2University Children’s Hospital Leipzig, Germany; 3Department of Endocrinology and Reproductive Diseases, Hôpital de Bicêtre, Hôpitaux Universitaires Paris-Sud, Assistance Publique-Hôpitaux de Paris and University Paris-Sud, Le Kremlin-Bicêtre, France; 4Clinic of Endocrinology and Diabetology, Children’s Memorial Health Institute, Warsaw, Poland; 5Faculty of Medicine and Health Sciences UJK, Kielce, Poland; 6Sandoz Biopharmaceuticals, Hexal AG, Holzkirchen, Germany Abstract: In 2006, the European Medicines Agency (EMA) approved Omnitrope® as a biosimilar recombinant human growth hormone (rhGH), on the basis of comparable quality, safety, and efficacy to the reference medicine (Genotropin®, Pfizer). Data continue to be collected on the long-term efficacy of biosimilar rhGH from several on-going postapproval studies. Particular topics of interest include efficacy in indications granted on the basis of extrapolation, and whether efficacy of growth hormone treatment is affected when patients are changed to biosimilar rhGH from other rhGH products. Data from clinical development studies and 10 years of postapproval experience affirm the clinical efficacy and effectiveness of biosimilar rhGH across all approved indications. In addition, the decade of experience with biosimilar rhGH since it was approved in Europe confirms the scientific validity of the biosimilar pathway and the approval process. Concerns about clinical effect in extrapolated indications, and also about the impact of changing from other rhGH preparations, have been alleviated. Biosimilar rhGH is an effective treatment option for children who require therapy with rhGH. Keywords: recombinant human growth hormone, Omnitrope®, biosimilar